Commodification and Westernization: Explaining Declining Nutritional Intake in Contemporary Rural China. (July 2015) - Xu, Zhun; Zhang, Wei; Oya, Carlos; Ye, Jingzhong; Zhang, Qian Forrest
<x xml:space="preserve">Abstract</x> Despite China's rapid growth in the past decade, Chinese rural residents suffer from a continuing decline of both calorie and protein intakes. We investigate the dramatic historical changes in nutritional intake in the Chinese countryside. There are two main explanations for the decline: first, the changing demographic and economic structure contributes to a lower demand for energy compared to traditional rural society; and, second, the rising cost of non‐food essential goods could lead to a squeeze in the food budget. Using both national‐level and provincial‐level data, we find evidence for both factors. We further argue that the current abnormally low level of nutritional intake is mainly due to commodification in the context of diet westernization. Rural residents' nutritional intake declines as they divert their consumption from relatively cheap sources of energy (grain and vegetable) to more expensive alternatives (meat and poultry) under a squeezed budget. The shocking failure of sustaining a healthy rural population is a unique manifestation of the contradiction in the Chinese agrarian relations.